1999
DOI: 10.1016/s0048-9697(98)00405-7
|View full text |Cite
|
Sign up to set email alerts
|

TOF-SIMS study of Cs + sorption on natural kaolinite

Abstract: The sorption of Cs q on natural kaolinite has been studied using time-of-flight secondary ion mass spectrometrẙ q Ž . TOF-SIMS . Depth profiling up to 70 A was performed to study the change in the amount of sorbed Cs as a function of depth in the kaolinite matrix. Quantitative determination of the amounts of primary cations in the kaolinite structure before and after sorption of Cs q ions was carried out to identify which cations are possibly taking part in the sorption process. The experimental results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…This fact reflects the instinct that tight hydrogen bonding between kaolinite layers restricts diffusion of adsorbed Cs to the interlayer sorption sites. This finding is in good agreement with those in other studies, in which Cs adsorption is reported occurring only at the first ten angstroms on the kaolinite surface [19].…”
Section: Xrd Analysis Of the Cs-loading Ltwsupporting
confidence: 93%
“…This fact reflects the instinct that tight hydrogen bonding between kaolinite layers restricts diffusion of adsorbed Cs to the interlayer sorption sites. This finding is in good agreement with those in other studies, in which Cs adsorption is reported occurring only at the first ten angstroms on the kaolinite surface [19].…”
Section: Xrd Analysis Of the Cs-loading Ltwsupporting
confidence: 93%
“…So far, a variety of studies have been devoted to characterizing various aspects of the sorption behavior of Cs + ion on kaolinite and on clinoptilolite, using a variety of characterization techniques [9][10][11][12][13][14][15][16][17][18]. In our earlier studies, the retention capacity of kaolinite toward Cs + was studied and compared with that of other clay minerals [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies, the retention capacity of kaolinite toward Cs + was studied and compared with that of other clay minerals [9]. A depth profiling study was also carried out to reveal the distribution of Cs + across the surface of kaolinite [10]. The applicability of kaolinite as a reactive barrier for Cs + retention was tested by other authors and the irreversibility of its uptake by kaolinite was discussed and compared with other clay minerals [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The ideal formula of kaolinite is Al 2 Si 2 O 5 (OH) 4 , and most minerals of the kaolin group appear to be close to ideal in composition. The structure of kaolinite consists of stacked units, each composed of one octahedrally coordinated sheet of aluminum ions and one tetrahedrally coordinated sheet of silicon ions (a 1:1 clay mineral).…”
Section: Introductionmentioning
confidence: 96%
“…ToF-SIMS was applied earlier to study the sorption behavior of these ions on natural clay samples rich in chloriteillite and bentonite clays [2,3] and of Cs + on natural kaolinite [4]. In dealing with geological samples, the most important difficulty associated with the application of surfacesensitive techniques stems from the heterogeneous nature of such samples.…”
Section: Introductionmentioning
confidence: 99%